Development of a worldwide ferry safety database utilizing relational database approach. Issue 4 (4th July 2019) - Xu, Siyu; Hu, Hao; Weisbrod, Roberta
ABSTRACT: Ferry transportation plays a crucial role in domestic and regional movement of people and goods between islands, along the coast and inland waterways, though this great dependence often contradicts with a high rate of ferry accidents, especially in Southeast Asia and the African Great Lakes region. Efforts to reduce ferry accidents are impaired by lack of complete and reliable data for accident analysis. This article analyzes the shortcomings of existing maritime accident databases from the perspective of ferry safety research and develops a dedicated worldwide ferry safety database using relational database approach to address the shortcomings and better facilitate ferry safety management—Ferry-SAFEDB. With this database structure, information related to ferry safety can be organized in a logical way that not only strengthens the efficiency and reliability of data maintenance, but also augments the amount of information to form a comprehensive information management platform and conduct data-driven analyses. Lastly, a sample database application is empirically conducted with the major ferry accidents over the past 17 years. The preliminary study shows that the proposed Ferry-SAFEDB is feasible and has the real-world implications for ferry safety efforts.